Pharmacodynamic Effects of Switching From Ticagrelor to Clopidogrel in Patients With Coronary Artery Disease: Results of the SWAP-4 Study. Issue 23 (5th June 2018) - Franchi, Francesco; Rollini, Fabiana; Rivas Rios, Jose; Rivas, Andrea; Agarwal, Malhar; Kureti, Megha; Nagaraju, Deepa; Wali, Mustafa; Shaikh, Zubair; Briceno, Maryuri; Nawaz, Ahmed; Moon, Jae Youn; et al.
Abstract : Background: Switching between different classes of P2Y12 inhibitors, including de-escalation from ticagrelor to clopidogrel, commonly occurs in clinical practice. However, the pharmacodynamic profiles of this strategy have been poorly explored. Methods: This was a prospective, randomized, open-label study conducted in patients on maintenance dosing (MD) of aspirin (81 mg/d) and clopidogrel (75 mg/d). After a 7-day run-in with ticagrelor (180 mg loading dose [LD] followed by 90 mg twice daily MD), patients (n=80) were randomized into 1 of 4 groups: group A, clopidogrel 600 mg LD 24 hours after the last MD of ticagrelor (C-600 mg-24h); group B, clopidogrel 600 mg LD 12 hours after the last MD of ticagrelor (C-600 mg-12h); group C, clopidogrel 75 mg/d MD 24 hours after the last MD of ticagrelor (C-75 mg-24h); and group D, ticagrelor 90 mg twice daily MD (T-90 mg twice daily). MD of the randomized treatment was maintained for 10±3 days. Pharmacodynamic assessments were performed at baseline, after run-in, and at 2, 24, 48, and 72 hours and 10 days with P2Y12 reaction units by VerifyNow; platelet reactivity index was assessed by vasodilator-stimulated phosphoprotein; and maximal platelet aggregation was determined by light transmittance aggregometry. Results: T-90 mg twice daily led to lower platelet reactivity than any clopidogrel regimen using all assays at all time points. P2Y12 reaction unit levels were similar between the C-600 mg-24h (group A) and the C-75 mg-24h (group C) ( P =0.29), including at 48 hours (primary end point; least mean difference, −6.9; 95% confidence interval, −38.1 to 24.3; P =0.66). P2Y12 reaction unit levels were lower with C-600 mg-12h (group B) than with C-75 mg-24h (group C; P =0.024). Maximal platelet aggregation over time was lower with both C-600 mg-24h (group A; P =0.041) and C-600 mg-12h (group B; P =0.028) compared with C-75 mg-24h (group C). Platelet reactivity index profiles paralleled those observed with P2Y12 reaction units. There were no pharmacodynamic differences for all tests between C-600 mg-24h (group A) and C-600 mg-12h (group B). In group C (C-75 mg-24h), platelet reactivity increased compared with baseline as early as 24 hours, reaching statistical significance at 48 and 72 hours and up to 10 days. These pharmacodynamic findings were delayed and blunted in magnitude with the administration of an LD, regardless of the timing of administration. Conclusions: De-escalation from ticagrelor to clopidogrel therapy is associated with an increase in platelet reactivity. The use of an LD before the initiation of an MD regimen of clopidogrel mitigates these observations, although this is not affected by the timing of its administration after ticagrelor discontinuation. Clinical Trial Registration: URL:https://www.clinicaltrials.gov . Unique identifier: NCT02287909. Abstract : Supplemental Digital Content is available in the text.